The community of inquiry framework and academic advising: online student perceptions - Stermer, Laura Louise Duncan (Kansas State University, 2018)
Perceptions of online undergraduate students on academic advising experiences were informed by the community of inquiry (COI) theoretical framework and categorized by a modified COI survey. The COI framework focused on students’ perceptions of their online learning environment, and acknowledged both the organizational (structural), transactional (collaborative view of teaching and learning), and social (isolation versus connected) challenges within online education. Indicators of COI included a decision-making process, open communication, shared personal meaning, and focused discussion. Thirty-four Likert-style survey items were used to measure student perceptions of three constructs within the COI framework: teaching presence, social presence, and cognitive presence. Cognitive presence included several stages: a sense of puzzlement, information exchange, connecting ideas, and resolution. Surveys were completed by online degree-seeking undergraduate students (N = 374, n = 87, response rate 23.3%) enrolled in spring one 2018 at a research one, land-grant institution. The analysis explored if COI was perceived in academic advising experiences. Perception of COI was categorized through self-reported preference of communication technologies (phone/TDD and web conferencing), demographic factors, and importance ranks on each COI item. Participants reported COI items as important, with variances between somewhat important and very important. Participants confirmed their perception of COI within academic advising with survey and open-ended comments. Analysis of data was conducted using a comparison of descriptive statistics, non-parametric tests, and qualitative coding of open-ended comments. Results of the data analysis revealed no significant differences (desirable) between advising technology (phone and web conferencing) and perception of COI. Descriptive characteristics revealed an increase in social presence with increased time with advisor and increased experience in completed online courses. This academic advising COI study found social presence was the highest perceived presence. Analysis of comments revealed themes confirming the rank of presence in the following order: social presence, teaching presence, and cognitive. The discussion of results focused on connections to current literature, as well as implications for future research and practice. Also, the new academic advising COI instrument (modified from original) offered a valid assessment tool for online advising, with the potential for use with a variety of advisor types, models, and institutions. Keywords: community of inquiry (COI), academic advising, higher education, online, assessment, web conferencing, social presence, teaching presence, cognitive presence, technology, online learning, student success, retention, and importance.
Keywords: Community of inquiry; Academic advising; Online learning; Higher Education; Adult Education; Educational tests and measurements